Research in early childhood education for sustainability : international perspectives and provocations - Julie Davis; Sue Elliot (Great Britain : Routledge, 2014)
Sustainability is a global issue that urgently needs addressing, and for which the most serious consequences are for children and future generations. This insightful research text tackles one of the most significant contemporary issues of our times - the nexus between society and environment - and how early childhood education can contribute to sustainable living.
Cluster 1. Ethics and Values -- Cluster 2. Historical and sociocultural contexts -- Cluster 3. Curriculum and pedagogy .
Includes index.
Keywords: EARLY CHILDHOOD EDUCATION--RESEARCH